Responsible Stakeholders: Key towards Successful Inclusion (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Inclusion is a mind set and attitude and a way of life that respects individuals with their needs as they are. It focuses on interdependency and quality education without discrimination. Each and every stakeholder is very valuable in realization of ultimatedreams of the inclusion and each stakeholder deserves same respect, despite of their educational status in the educational process. It is very important for stakeholders to hold positive attitudes and beliefs about inclusion since it affects the extent to which philosophy of inclusion is implemented in the school. All the stakeholders should pay attention to both excellence and equity in the education. A change in attitude of stakeholders is very much needed so that diversity is celebrated everywhere not in the school only. Since inclusive classroom is heterogeneous having children with diverse needs, it is a challenge to manage such classroom for teachers and for educational administrators also. It is possible only when all the stakeholders such as teachers, parents, children, community members, educational administrators, non academic staff, resource teachers have interest in the process of education and supports each other so that the enterprise of education become successful. This paper clearly identifies the roles and responsibilities of various stakeholders in the process of education. Role of every stakeholder has been discussed in detail which will work as guidelines for them. All stakeholders must have coordinated collaboration with each other to make positive inclusive environment in the process of education. If any one of the stakeholders doesn't show commitment then work and efforts of other stakeholders also will not give thedesired output towards complete and successful inclusion.